2019
DOI: 10.1177/0300060519853655
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a probiotic drink containing Lactobacillus casei strain Shirota on dental plaque microbiota

Abstract: Objective To investigate the effects of a probiotic drink containing Lactobacillus casei strain Shirota on dental plaque microbiota. Methods Caries-free young adults were administered a probiotic drink containing L. casei Shirota (Yakult) three times on day 1, then once daily for 28 days. Dental plaque samples were collected and analysed by 16S rRNA sequencing before (day 1), during (day 2), and one day following intervention (day 30). Results Out of samples from 10 included participants, 256 814 sequences pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Veillonella uses lactate and metabolizes it to weaker acids, such as acetate and propionate. In a recent clinical study to investigate the effects of a LcS probiotic drink on dental plaque microbiota, the relative abundance of Veillonella was significantly increased following a 28-day LcS intervention [ 39 ]. Rikenellaceae is associated with schizophrenia [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Veillonella uses lactate and metabolizes it to weaker acids, such as acetate and propionate. In a recent clinical study to investigate the effects of a LcS probiotic drink on dental plaque microbiota, the relative abundance of Veillonella was significantly increased following a 28-day LcS intervention [ 39 ]. Rikenellaceae is associated with schizophrenia [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…L. salivarius inhibits S. mutans and C. albicans double-species caries biofilms by decreasing the amount of caries pathogenic species and reducing the biofilm mass in vitro [5]. Another study indicated that after taking a probiotic drink containing L. casei strain Shirota for 28 days, the abundance of Veillonella and Kingella increased significantly, while the abundance of some other bacteria related to caries was decreased in the oral cavity of young adults, as shown by the 16S rRNA sequencing results [7]. Different probiotic strains may prevent caries via different mechanisms, including the inhibition of cariogenic bacteria growth [8] and pathogenesis, exopolysaccharide (EPS) production reduction [9], quorum sensing inhibition [10], and reduction of the expression of key metabolic and virulence genes [11].…”
Section: Introductionmentioning
confidence: 92%
“…Rosier et al [2018] found that the adhesion ability of S. mutans to teeth and oral mucosal surfaces was directly reduced by the agglutination reaction of some probiotics, and these probiotics can also regulate the composition of salivary glycoproteins to maintain the oral microecological balance. Continuous consumption of probiotic drinks containing Lactobacillus casei can significantly increase the abundance of nitrate-reducing bacteria, such as Veillonella and Kingella, because these probiotics can compete for adhesion sites, nutrients, and growth factors with bacteria that induce caries [Hu et al, 2019]. However, other studies have reported that the advantage of probiotics may not be significant in the prevention of caries and that, in some instances, they may not impact the occurrence of dental caries.…”
Section: Probioticsmentioning
confidence: 99%